9th Five Year Plan 1997-2002 Volume-III Sector : Transport Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1997)
Providing warehouses facilities at Port Blair Port is an important aspect of the scheme as the existing facilities are enough to tackle the situation. Due to paucity of space in the port area and increase in import of general cargo, the cargo stacked at open space are not only exposed to atmospheric conditions but also to monoonic weather. Heaping of cargo over Wharves/jetties also endanger the safety of the structure standing on the piles .Thus warehouses are very much essential to overcome the cluttering of cargo a ports.
Andaman and Nicobar Administration, Planning Department